Quality indicators in a hematology laboratory- a retrospective analysis - Kashyap, Akriti; Kaur, Gurpreet; Tripathi, Preeti; Sen, Arijit (International Journal of Advances in Medicine, 2020)
Background: Quality indicators are objective parameters which help to assess the effectiveness of the working system in any laboratory. Aim and objective were to study 7 common quality indicators in the hematology laboratory of a tertiary care centre. Methods: It was a retrospective analysis over a period of two and a half years (Jul 2017- Dec 2019). The following 7 QIs were analysed- sample rejection rates, sample redo rates, routine turnaround time (TAT), critical reports and their TAT, corrected reports, staining quality assessment and concordance in EQAS programme. The QI rates were calculated on monthly (or as specified) basis and trends were analysed. P value <0.05 was considered significant. Results: The final result showed average routine, urgent and critical turnaround time to be 6.5 hrs, 1.1 hrs and 3.4 hrs respectively. The other QIs were as follows - sample redo rates (3.8%), sample rejection rates (3.2%), corrected report rates (before validation– 8.5%, after validation- 1.2%) staining quality (unsatisfactory days rate- 4.5%), 98% corcordant performance in EQAS. Over the study period, a significant downward trend was noticed in TAT and sample rejection rates (p value=0.001 and 0.007 respectively). Number of monthly critical alerts showed an upward trend (p value=0.045) which could be attributed to increased awareness amongst lab staff. Redo rates showed no significant change in trend over study period. Conclusions: Quality indicators help in self-assessment and self-improvement. Their continuous monitoring is mandatory to have a tight quality check system and better clientele satisfaction.